Analisis Pengaruh Debt To Equity Ratio, Current Ratio, Dan Total Aset Turnover Terhadap Kinerja Keuangan (Studi Kasus Pada Perusahaan Property dan Real Estate yang Terdaftar di BEI Tahun 2015-2020) - Kusumawati, Erlin; Widaryanti, Widaryanti (Jurnal Ilmiah Fokus Ekonomi, Manajemen, Bisnis & Akuntansi (EMBA), 2022)
Property and real estate is one of the investment alternatives that investors are interested in. The property and real estate industry is an industry with good prospects considering the rapid increase in products and incomes of the people, thus encouraging an increase in demand and supply of housing. The property and real estate sector is the most strategic land for investment that will provide high profits. The purpose of this study was to analyze the effect of debt to equity ratio, current ratio, and total asset turnover on financial performance partially and simultaneously. This study uses a population of property, real estate and building construction companies listed on the Indonesia Stock Exchange (IDX) during 2015-2020. The sampling technique was purposive sampling method. The data analysis method used is multiple regression. The results of this study are: The debt to equity ratio has a significant negative effect on financial performance with a significance value of 0.001 <0.05. The current ratio has a significant positive effect on financial performance with a significance value of 0.004 <0.05. The total asset turnover ratio has a significant positive effect on profit growth, with a significance value of 0.000 <0.05.Keywords : Debt to Equity Ratio, Current Ratio, Total Asset Turnover and Financial Performance